2000
DOI: 10.1093/jnci/92.2.154
|View full text |Cite
|
Sign up to set email alerts
|

Intake of Flavonoids and Lung Cancer

Abstract: If replicated, particularly in prospective studies, these findings would suggest that foods rich in certain flavonoids may protect against certain forms of lung cancer and that decreased bioactivation of carcinogens by inhibition of CYP1A1 should be explored as underlying mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
312
2
21

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 511 publications
(345 citation statements)
references
References 43 publications
10
312
2
21
Order By: Relevance
“…For example, chronic quercetin treatment was shown to lower blood pressure or prevent the development of hypertension in various experimental models [Duarte et al, 2001;Perez-Vizcaino et al, 2006]. Consumption of quercetin, enriched in onions and apples, was found to be inversely associated with lung cancer risk [Le Marchand et al, 2000]. Furthermore, quercetin was shown to inhibit cancer growth and induce apoptosis in animal models [Mouria et al, 2002].…”
Section: Discussionmentioning
confidence: 99%
“…For example, chronic quercetin treatment was shown to lower blood pressure or prevent the development of hypertension in various experimental models [Duarte et al, 2001;Perez-Vizcaino et al, 2006]. Consumption of quercetin, enriched in onions and apples, was found to be inversely associated with lung cancer risk [Le Marchand et al, 2000]. Furthermore, quercetin was shown to inhibit cancer growth and induce apoptosis in animal models [Mouria et al, 2002].…”
Section: Discussionmentioning
confidence: 99%
“…General characteristics of case-control and cohort studies are shown in Tables 1 and 2, respectively. Case-control studies were published between 1994 and 2014; three were conducted in Italy (13,19,22) , two each in Iran (10,15) , China (12,23) and Australia (14,29) , and one each in Poland (16) , Spain (11) , Czech Republic (17) , Brazil (18) , UK (20) , India (24) , Hawaii (25) , Mexico (26) , Sweden (27) and Uruguay (28) . One was a multinational study conducted in nine countries worldwide (Italy, Spain, Poland, Northern Ireland, India, Cuba, Canada, Australia and Sudan) (21) Cohort studies were published between 1998 and 2012; nine were conducted in the USA (30,31,(34)(35)(36)(37)39,40,45) and eight were conducted in Europe (32,33,38,(41)(42)(43)(44)46) .…”
Section: Literature Searchmentioning
confidence: 99%
“…Previous studies have indicated that naringenin has anti-cancer effects; however most studies focused on its role in primary tumor prevention (So et al, 1996;Le Marchand et al, 2000;Kanno et al, 2005), and few investigated its antimetastatic effects. We previously found that naringenin could attenuate bleomycin-induced pulmonary fibrosis by improving the immunosuppressive environment .…”
Section: Introductionmentioning
confidence: 99%